1978
DOI: 10.1128/aem.35.2.323-328.1978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polychlorinated Biphenyls on Growth and Respiration of Heterotrophic Marine Bacteria

Abstract: A number of marine bacterial isolates from both near-shore and open-ocean environments were tested for growth inhibition with exposure to low concentrations (1 to 100 ,ug/liter) of Aroclor 1254, a commercial mixture of polychlorinated biphenyls (PCBs). Of over 17 bacterial cultures tested, growth of only two openocean isolates, one a pseudomonad and the other a tetrad-forming coccus, was consistently inhibited by Aroclor at concentrations as low as 10 ,ug/liter (10 ppb). Growth inhibition was dose dependent ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…By 4 h posttreatment, RNA/protein, DNA/protein, and DNA/RNA ratios were similar in the total cell fraction from an untreated control culture and one in which growth was completely inhibited. Furthermore, cells whose growth was stopped by PCBs grew at normal rates without a lag when transferred to PCBfree medium (1). These findings indicated that Aroclor-treated cells did not selectively degrade their nucleic acids or proteins during the period their growth was arrested.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…By 4 h posttreatment, RNA/protein, DNA/protein, and DNA/RNA ratios were similar in the total cell fraction from an untreated control culture and one in which growth was completely inhibited. Furthermore, cells whose growth was stopped by PCBs grew at normal rates without a lag when transferred to PCBfree medium (1). These findings indicated that Aroclor-treated cells did not selectively degrade their nucleic acids or proteins during the period their growth was arrested.…”
Section: Resultsmentioning
confidence: 91%
“…In this medium without Aroclor it grew in chains of from 2 to 10 cells, and, with 10 to 50,g of PCBs per liter present, it grew in long filaments. In seawater-Casamino Acids-yeast extract medium (SWCAA) (1), it grew as single, motile cells in the absence of PCBs and in short chains of cells when Aroclor was present at 10 to 100 ,tg/liter. SWCAA medium was developed in response to the need for accurate estimates of cell numbers in the work to be described.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More ecological approaches were conducted on marine or fresh water with bacteria [3], algae [4] and protozoa [5,6]. The last authors tested the response of indigenous protozoan communities to complex river effluent supply: they observed the colonization of artificial substrates supplemented or not by the effluents by the protozoa in laboratory microecosystems and then, they validated the laboratory predictions using similar sampling methods in the field.…”
Section: Introductionmentioning
confidence: 99%